(3bUjOIs - (3MGJe GdWGFjs ((3YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf YHO GdSdGe GdYHGSi s)
(3ChdgG (B:s
(3CJYQa HGdLQYGA Ce CfJ JfcQ OjGQ JabgG QjGM hCYGUjQG s
(3BNQgG (B:s
(3hdjS aNGQ GdeDef MSf UhHg hdG cf jMSf GdaUd jHbi hjPcQ JeJ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B15s
(3HgG Jedc HGSe YHO Gddg Hf YHO GdhGMO Hf YHO GddWja Hf TYjH Hf YHO GdSdGe hjQLY JGQjNgG Edi SfI (B1294 (3g`s
(3bQf GdfSN (B:s
(3GdbQf GdKGdK YTQs
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdYHGSjI (B_ (3GdHUQI (B(7(3O(B) s
Keywords: (3GdeLGejYs